Determination Of Sewage Sludge Composition As Partial Substitute In Clay Bricks - Wong, Calvin Hong Kiat (2002)
Sludge is an unavoidable by-product of wastewater treatment and creates problem of disposal. Generally, dewatered sludge is disposed of by landfilling. However, this option might not be appropriate due to land limitation and stringent environmental regulations imposed. Therefore, a joint effort study between IWK and UPM was carried out to investigate the possibility of incorporating dried sludge in building bricks at laboratory level as an alternative means of sludge disposal while being an innovative way of making construction materials. Bricks were produced with sludge additions ranging from 10 to 40% by dry weight. The texture and finish on the surface of sludge-amended clay bricks were rather poor. Nonetheless, they were every bit as attractive due to being light red in colour and odourless. As for physical and chemical properties, bricks with up to 40wt% sludge were capable of meeting the appropriate technical standards. However, bricks with more than 30wt% sludge amendment were not recommended for use since they were brittle and easily broken even when handled gently, Heavy metal leaching test carried out on crushed brick samples to simulate extreme environmental conditions resulted in leachate losses way below the USEP A extraction procedure regulatory limits. Therefore, all the bricks with different proportions of sludge were classified as non-hazardous materials and should be safe for use as a building material. In this study, which used the classical handmoulding method to compact the brick specimens in custom-made wooden moulds, the quality of bricks produced were quite varied and the structural properties results obtained were less than satisfactory compared to that of other researchers (using extruders) mainly due to the more uniform and higher moulding pressure applied on their bricks. However, results obtained in this study would serve as a guide to subsequent full-scale studies. On top of that, some anticipated improvements for future full-scale brickrnaking process based on the preliminary results, to produce better quality bricks, was given due attention. Knowing that the technical criteria of the bricks could be optimized, however, this process may require consumer education and regulatory assistance for long term success and acceptance.